Effects of Methanol Extract of Gongronema Latifolium Leaves on Glycaemic Responses to Carbohydrate Diets in Streptozotocin-Induced Diabetic Rats - C, Udeh Sylvester M.; C, Nwodo O. F.; E, Yakubu O.; M, Ale E.; J, Parker E.; S, Egba; E, Anaduaka; P, Ugwu O.; M, Ude C.; J, Iornenge T.; J, Danjuma (Darul Yasin Al Sys, 2024)
The search for natural plant extract as an alternative therapy to diabetes management has received enormous recognition globally. In this study, the effects of the methanol extracts of Gongronema latifolium leaves (GLE) on glycaemic responses to carbohydrate diets [obtained from cassava (Manihot esculenta), yam (Dioscorea rotundata) and plantain (Musa paradisiaca)] in streptozotocin-induced diabetic rats was investigated. Forty five adult male Wistar albino rats were induced diabetes by intraperitoneal (i.p.) injection of streptozotocin (STZ) (65 mg/kg b.w.) dissolved in citrate buffer, pH 4.5. The diabetic rats were divided into nine groups of 5 animals each. Group 1: the Positive control (diabetic, untreated) was fed with water only, group 2: the standard control (diabetic, treated) received 2.50mg/kg b.w of glibenclamide, a standard drug for diabetes, group 3, 4 ad 5 (carbohydrate diets treated only) were orally fed with 200 mg/kg b.w. of cassava diet, 200 mg/kg b.w. of yam diet and 200 mg/kg b.w. of plantain diet respectively, group 6, 7 ad 8 (GLE mixed with carbohydrate diets treated) were orally fed with 200 mg/kg b.w. of cassava mixed with 100 mg/kg b.w. of GLE, 200 mg/kg b.w. of yam mixed with 100 mg/kg b.w. of GLE and 200 mg/kg b.w. of plantain mixed with 100 mg/kg b.w. of GLE respectively, while group 9 (GLE treated only) was fed with 100 mg/kg b.w. of GLE only. The experiment lasted for 21 days with free access to feed and water. Animals’ weights were measured on weekly basis as well as estimation of fasting blood sugar (FBG) and postprandial blood glucose (PBG). Results revealed that, administration of carbohydrate diets led to a significant (p < 0.05) decrease in body weights of the diabetic rats fed with carbohydrate diets. Conversely, administration of the GLE mixed with the diets caused a significant (p > 0.05) increase in body weights of the diabetic rats compared to the positive control. However, treatment with GLE alone showed a more effectuality which is comparable to that of the standard drug in restoring weight loss. In addition, the results of blood glucose estimation revealed a significant (p < 0.05) elevation in both fasting blood glucose (FBG) and Postprandial blood glucose (PBG) in animals fed with carbohydrate diets when compared to the positive control, but a significant (p < 0.05) decrease was observed in both parameters upon the admiistration of GLE mixed with carbohydrate diets. Similarly, administration of GLE alone caused an increase in both FBG and PBG which was significant (p < 0.05) compared to group fed with GLE mixed with carbohydrate diets. Howbeit, GLE elicited more potent and efficacious response when compared to the standard drug. Herein, we therefore deduce that methanolic extracts of G. latifolium leaves exhibited hypoglycaemic responses in the diabetic rats and the plant could be a worthwhile candidate in the design of a potent antidiabetic drug.